Teacher empowerment : an interpretive study of the experience of Asian migrant teachers in Western Australia - Law, Geoffrey Ka Hoo (Curtin University, 2010)
This research was prompted by arguments about the importance of empowerment in professional praxis of school practitioners and related legislations, namely, the Better Schools’ reform in 1987 and the WA Charter of Multiculturalism in 2004, and by persistent feelings of disempowerment and inefficacy I had experienced as an Asian migrant school practitioner in WA Government schools. Attributing cause to others is always easier than looking to ourselves for the root of our problems. Guided by the innovative concept of a research multi-paradigmatic design space, I adapted methods from the interpretivist-constructivist and critical paradigms, and embarked on a process of critical self-reflection aimed at gaining an understanding of my feelings of disempowerment and inefficacy.Complementing this autoethnographic study, selfreflections of three other Asian migrant school practitioners were included to gauge the degree of consonance of feelings amongst us as I shared my lived experience with them. The sharing of our experiences over a four-year period revealed that lack of respect and support from key stakeholders of the school system had been one of the root causes of our negative feelings, and that this perception was related to cultural dissonance between our collectivist Asian culture and the more individualistic culture of WA school communities.A natural response to the findings was a search for ways of minimizing the cultural dissonance. This research is as much a self-initiated change as a ‘political outreach’ aimed at instigating further discussion and debate as a catalyst for system-wide policy initiative to address the issue of cultural dissonance which is considered to be a key to reducing of feelings of disempowerment and inefficacy amongst Asian migrant teachers in WA Government schools. This research has been an emancipating and enlightening personal experience but it was not without limitations and problems.